Performansi Pendingin Termoelektrik Alat Transportasi Ikan Segar pada Berbagai Tegangan - Tri Nugroho Widianto; Arif Rahman Hakim (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
Thermoelectric performance test of refrigerated fish container at various voltages was conducted. Performance test aims to determine temperature of heat pipe, heat sink, room container and electric current requirements of thermoelectric refriferator at various voltages. Thermoelectric refrigerator composed of two pieces peltier elements, aluminiums bracket, fan, heat sink and heat pipe. Thermoelectric refrigerator was placed at the top of fish container. Various voltages used were 8 V, 10 V, and 12 V. Parameters measured were the amount of electric current through the thermoelectric, temperature of heat sink, heat pipe and room container. Room container temperature could be reached on 12, 10 and 8 V were 14, 16 and 17 °C respectively. Heat sink temperature on 12 V was -0.1 °C and temperature on 8 and 10 V were 3-4°C. Heat pipe temperature on 12 and 10 V reached 30-31 °C, while temperature on 8 V was 27 °C. The electric current requirements on 12, 10 and 8 V were 6.3, 4.8 and 3.8 A with energy requirements of refrigerated fish container were 75, 48 and 30 watt respectively. The cooling capacity of peltier module on 12 V was 12.5 W, while the cooling capacity on 10 and 8 V were 10.5 W respectively.ABSTRAKUji performansi pendingin termolektrik alat transportasi ikan segar pada berbagai tegangan telah dilakukan. Uji performansi dilakukan untuk mengetahui suhu heat pipe, heat sink serta ruang peti insulasi serta kebutuhan listrik sistem pendingin pada berbagai tegangan. Sistem pendingin termoelektrik tersusun dari dua buah elemen peltier, bracket alumunium, fan, heat sink dan heat pipe. Pendingin termoelektrik dipasang di bagian atas peti insulasi. Uji performansi dilakukan pada tegangan 8, 10 dan 12 V. Parameter yang diukur adalah jumlah arus listrik yang melalui sistem pengingin, suhu heat sink, heat pipe dan suhu ruang peti insulasi. Suhu ruang peti insulasi yang dicapai pada tegangan 12, 10 dan 8 V berturut-turut sebesar 14, 16 dan 17 °C. Suhu heat sink yang dicapai pada tegangan 12 V sebesar -0,1 °C, sedangkan pada tegangan 8 dan 10 V tidak jauh berbeda yaitu antara 3-4 °C. Suhu heat pipe yang dicapai pada tegangan 12 dan 10 V tidak jauh berbeda yaitu sekitar 30-31 °C, sedangkan pada 8 V sebesar 27 °C. Kebutuhan arus listrik sistem pendingin pada tegangan 12, 10 dan 8 V sebesar 6,3; 4,8 dan 3,8 A dengan kebutuhan energi berturut-turut 75, 48 dan 30 Watt. Nilai cooling capacity elemen peltier pada tegangan 12 V sebesar 12,5 W, sedangkan pada tegangan 10 dan 8 V sebesar 10,5 W.